Integrated energy conversion units in nanoscale frameworks induce sustained generation and amplified lethality of singlet oxygen in oxidative therapy of tumor. Issue 6 (23rd November 2022) - Zhu, Jing; Ding, Tao; Jin, Kaifei; Xing, Yuxin; Huang, Jixi; Xia, Daqing; Cai, Kaiyong; Zhang, Jixi
Abstract: Reactive oxygen species (ROS) driven endoplasmic reticulum (ER) stress is highly promising for tumor therapy but restrained by the nondurable introduction and limited lifetime of oxidative species. Here, a therapeutic nanosystem with sustainable ROS generation ability was developed by accommodating luminol derivatives (L012) in hyaluronic acid‐modified metal‐organic frameworks of Fe 3+ and porphyrin ligand (TCPP). After particle accumulation in the tumor, ∙OH radicals from Fe 3+ sites catalyzed conversion of H2 O2 can react with confined L012 transducers to generate chemiluminescence (CL). Because of the distance constraints, the CL energy was significantly extracted (96%) by adjacent TCPP and further activate oxygen to long‐lifetime singlet oxygen ( 1 O2 ), whose yield can be further boosted by the catalase‐like activity of the frameworks. By regulating the substrate consumption through energy conversion, the cascade process resulted in increased ROS levels (2.4‐fold) and sustainable oxidation (24 h), which induced continuously accumulated ER stress, high autophagic levels, and amplified lethality against the tumor. This work opens a new avenue to explore reticular nanostructures with complementarily arranged and synergistically spaced conversion units in advancing ROS therapy. Abstract : A nanoscale cascade system is fabricated by Fenton‐like catalysts, chemiluminescence reagents, and porphyrin derivatives. The complementary cascade can regulate the consumption of the substrate and sustainably generate 1 O2 through energy conversion. Meanwhile, the catalase‐like catalytic activities can further realize O2 self‐sufficiency. Furthermore, the enhanced reactive oxygen species stress can cause persistent endoplasmic reticulum stress promoting autophagy and apoptosis.